1996
DOI: 10.1111/j.1469-8137.1996.tb04362.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses to water stress in an ABA‐unresponsive hybrid poplar (Populus koreana×trichocarpa cv. Peace) II. Hydraulic properties and xylem embolism

Abstract: SUMMARYWe compared the xylem hydraulic properties of potted cuttings of two poplar clones {Populus koreana x trichocarpa cv. Peace and P. x etiratnericana cv. Robusta) known to differ in their sensitivity to ABA and in their ability to close their stomata during a period of drought. 'Robusta' can control stomatal aperture, whereas 'Peace' can only close the stomata of immature leaves. 'Peace' did not exhibit any specific hydraulic property that could compensate for its lack of response to a water deficit. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 24 publications
(38 reference statements)
2
38
0
Order By: Relevance
“…Similarly, exogenous ABA application alone has been shown to enhance drought tolerance in previous studies (Gibson et al, 1991;Wan and Zwiazek, 2001). Studies with an ABA-unresponsive hybrid poplar also confirmed a role for ABA in development of drought tolerance (Cochard et al, 1996). Accordingly, ABA may function as a trigger to initiate the process for drought adaptation and enhance drought tolerance in most groups of higher plants.…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, exogenous ABA application alone has been shown to enhance drought tolerance in previous studies (Gibson et al, 1991;Wan and Zwiazek, 2001). Studies with an ABA-unresponsive hybrid poplar also confirmed a role for ABA in development of drought tolerance (Cochard et al, 1996). Accordingly, ABA may function as a trigger to initiate the process for drought adaptation and enhance drought tolerance in most groups of higher plants.…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, previous studies also showed that exogenous ABA application alone [14,18,31,32] or endogenous ABA content increased rapidly under water stress [20,33] could enhance drought tolerance in woody plants. ABA is a hormonal stress signal that moves in the xylem from the root to the different parts of the shoot where it regulates transpirational water loss and leaf growth [34][35][36].…”
Section: Discussionmentioning
confidence: 93%
“…In the second, trees favour a large stomatal conductance g s ; in the last they seem to close their stomata before a significant degree of embolism can occur. (from Cochard, unpublished collected results): PT = Populus trichocarpa, [21]; JR = Juglans regia, (Cochard and Améglio, unpublished); VM = Vaccinum corymbosum, [6]; FS = Fagus sylvatica, [24]; PP = Prunus persica, [4]; PH = Pinus halepensis, (Froux and Huc, unpublished); QR = Quercus robur; QP = Quercus petraea, [20]; PA = Picea abies, [69] climatic conditions. A significant progress on that field will be realized by improving our knowledge about the anatomical connections between the root system and the shoot.…”
Section: Discussionmentioning
confidence: 99%
“…Cochard et al [21], studied the water relations of a Populus hybrid (trichocarpa × koreana) known to lack efficient stomatal closure in the presence of soil water stress. It was actually found that only stomata in mature leaves were unresponsive to water stress.…”
Section: Stomatal Closure Can Prevent "Runaway Embolism"mentioning
confidence: 99%